A Good Aesthetic Outcome After Gross Total Tumor Resection in Combination With the Skull Reconstruction on Giant Epidermal Cyst Involving Both Intracranial and Extracranial Tissues. Issue 1 (January 2022) - Shi, Yifeng; Zhang, Chenyang; Huang, Hua; Hu, Xin; Liu, Yanhui
Abstract : Abstract: Epidermal or epidermoid cysts are 1 of the most frequent benign masses, they rarely grow to a huge size, and only a few cases have been reported. We report a rare case of a 52-year-old man with giant neoplasm growing invasively in the frontal region, including both intracranial and extracranial extensions, and caused extensive brain deformation and skull lesions. It is worth noting that the patient did not present any significant neurological symptoms and deficits for more than 40 years on admission. A combination of gross total tumor resection and cranioplasty was performed. The patient was satisfied with the results of the surgery, and no evidence of recurrence or complications were found in the 2 years follow-up. The authors reported the case not only to propose the first-stage aesthetic treatment option for this unusual mass on the scalp but also hinted at the vigilance and importance of systematic monitoring of the small skull mass for avoiding the potential risk of tumor progression, malignant transformation, operative trauma, and financial burden.